Evidence of altered structural and secretory glycoconjugates in the jejunal mucosa of patients with gluten sensitive enteropathy and subtotal villous atrophy. Issue 6 (June 1989) - Vecchi, M; Torgano, G; de Franchis, R; Tronconi, S; Agape, D; Ronchi, G
Abstract : The pattern of lectin histochemistry in formalin fixed, paraffin embedded normal jejunal and subtotal villous atrophy specimens from patients with gluten sensitive enteropathy were compared. There was no significant difference in the binding pattern of five lectins (Arachis hypogaea, Canavalia ensiformis, Lens culinaris, Phaseolus vulgaris and Triticum vulgaris) between normal and abnormal specimens. There were significant changes in the binding pattern of three lectins (Dolichos biflorus, Ulex europaeus, Ricinus communis), with special reference to goblet cells staining. These changes were present in all the specimens studied, regardless of the clinical diagnosis of dermatitis herpetiformis or coeliac disease. Dolichos biflorus reactive goblet cells were significantly decreased (p less than 0.001) in abnormal tissue and confined to the luminal edge of the mucosa. Strong reactivity of goblet cells in abnormal tissue was recorded with Ricinus communis and Ulex europaeus, lectins that bind to few or no goblet cells in normal tissue. These findings show that modifications of structural and secretory glycoconjugates occur in the jejunal mucosa of patients with gluten sensitive enteropathy.